Hubungan Kompetensi Pedagogik terhadap Kinerja Guru Taman Kanak-kanak - Elmida, Elmida; Saridewi, Saridewi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
Teacher's pedagogic competence is closely related to teacher performance. If the competency is good, the teacher's performance will also be good. This study was conducted to determine the relationship between pedagogic and performance competencies in the kindergarten teacher of the Gugus Seroja Kindergarten in Kuranji, Padang City. The research conducted is correlational research which aims to see the relationship of competence to teacher performance variables. The study uses a quantitative descriptive correlation analysis approach, trying to tell the problem solving that exists by presenting data, analyzing and interpreting it. Sampling is done by Total Sampling technique. The research instrument was a questionnaire or questionnaire. The data analysis technique is to use two similarity tests on average with t test statistics to find out whether there is a significant relationship between pedagogic competence and teacher performance. Based on the results of data analysis can be stated research conclusions. First, pedagogic competence has a positive and significant effect on teacher performance. In other words, the teacher's performance in the Kindergarten of Gugus Seroja, Kuranji, Padang City is influenced by the pedagogical competence of the teacher. Second, pedagogic competence has a positive and significant effect on teacher performance. With good competency, the teacher will be enthusiastic in the task of achieving a level of effectiveness, so as to improve teacher performance, the hypothesis can be accepted.